Friday

April 18, 2014

April 18, 2014

Posted by **leo** on Wednesday, October 24, 2007 at 4:32pm.

3( y - 4 ) - 2 ( 5 - 6y )

= 3 x y = 3y, 3 x - 4 = - 12

-2 x 5 = -10, - 2 x -6y = - 12y

Therefore, 2y -12 -10 -12y

If I am wrong can you advise where I am going wrong .Thanks !!!

- Maths ..equation -
**Reiny**, Wednesday, October 24, 2007 at 4:36pmYou should not write your solutions in bits and pieces, besides some of your steps are not correct.

Here is how it should look:

3( y - 4 ) - 2 ( 5 - 6y )

= 3y - 12 - 10 + 12y

=15y - 22

**Related Questions**

Math 012 - im having trouble with this one too. 6y-8=-6+3y+13 heres what ive ...

mat 117/algebra - Find the GCF of each product. Please show the steps so I can ...

Pre-Algebra - 6y+8=-3y-28 Here is what I did 6y+8-8=-3y-28-8 6y=-3y+20 6y-(-3y...

maths - Simplify the expression. 1. 3y-(6y+2)(-y) 2. (-7x+^2)(-x)+x^2 3. 3y/2 ...

For MathMate - Hi! So i posted a question yesterday and I worked on but before i...

Pre-Calculus - Solve by using the substitution method 1.x=-3y+4 and 3x+9y=12 3(-...

math - A linear system may have a unique solution, no solution, or infinitely ...

Mat 116 - Solve the system by graphing 8x-6=-18 6y-8x=18 divide 1 equation by 2 ...

Algebra - Find the GCF of each product. (6y^2-3y)(y+7) I think it is 3y. I'm not...

Math - What do these factor out too?? (3w^2+w)(-6w-2) (3y^2+y)(6y+2) (6y^2+2y)(-...